Changes in Semen, Hormonal profile and Testicular Morphology of West African Dwarf Goat Bucks treated with Danazol - Lukman Oladimeji Raji; Mohammed Babashani; Ganiyu Jimoh Akorede; Aishat O Olatunji; Fatima Sanusi; Yusuf Idris; Khalid Tahlia Biobaku (Turkish Journal of Agriculture: Food Science and Technology, 2020)
This study was carried out to investigate the changes in semen characteristics, hormonal profile and testicular morphometry of West African Dwarf (WAD) goat bucks treated with danazol. For this purpose, eighteen matured WAD bucks average of about two years were randomly divided into groups A, B and C comprising of six bucks per group. Group A was the control while B and C bucks were given danazol at a dose rate of 20mg/kg body weight orally daily for four weeks. The group B bucks’ testes were harvested thereafter for gross and histo-morphometric studies while those of group C were left intact but danazol treatment was withdrawn for four more weeks. The bucks’ semen samples (collected by electro-ejaculation) and hormonal samples (taken via the jugular vein) were analyzed. The semen characteristics studied included color, volume, mass activity, motility, percentage normal live-dead ratio, morphology and concentration; while the hormones studied included testosterone, follicle stimulating hormone and luteinizing hormone. Results show that there were significant decreases in semen characteristics of group B and C bucks compared with those of group A in the first four weeks. The semen characteristics of the group C bucks were reversed to normal range (similar to those of group A bucks) two weeks after danazol treatment was withdrawn. Similar results were observed with the hormonal studies. In conclusion, danazol caused a reversed reduction in sperm cells characteristics suggesting its possible use as a contraceptive in WAD goat bucks.